Prevalence and quality of life associated with erectile dysfunction and lower urinary tract symptoms: a cross-sectional study - Felipe Jun Kijima; Liz Cristina Motta; Jean Sousa Cavalcante; Lucas Jordão; Carlos Eduardo Dias Olioze; Plinio Takashi Karubi Palavicini Santos; João Carlos Leite da Cruz; Luis Expedito Sabage; Gabriel Araújo Medeiros; Alessandra Mazzo; Aguinaldo Cesar Nardi (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Genitourinary health significantly affects the quality of life of men, particularly those in middle age. Recent studies have shown that more than half of the men aged over 40 years experience some degree of low urinary tract symptoms (LUTS) or erectile dysfunction (ED). OBJECTIVE: To assess the prevalence of ED and LUTS in middle-aged men and correlate this with quality of life data. DESIGN AND SETTING: A cross-sectional study was conducted in a municipality in the countryside of São Paulo. METHODS: A trained team collected data between July 2021 and August 2022 through face-to-face interviews using a characterization instrument, International Prostate Symptom Score (IPSS), International Index of Erectile Function-6 (IIEF-6), and World Health Organization Quality-of-Life Scale. RESULTS: The study included 375 male participants with a median age of 53 years (interquartile range [IQR] 38.5-66). The IIEF-6 showed the presence of some degree of ED in 51.1% (n = 188) of patients, with a median score of 25 (IQR 21-29). The IPSS revealed that 35.2% (n = 132) of the patients had some degree of LUTS, with a median score of 5 (IQR 2-11). The urological questionnaires had a direct proportional correlation with age (P < 0.001) and significant differences between the medians of different marital statuses (P < 0.001). The presence or severity of these disorders was inversely correlated with the individuals’ quality of life (P < 0.001). CONCLUSIONS: ED and LUTS significantly correlated with the quality of life, marital status, and age in men.